A STUDY OF INTERNET FINANCIAL REPORTING (IFR) IN INDIAN BANKING SECTOR - Nayaka, Dr. Devaraja (The journal of contemporary issues in business and government, 2021)
The Internet offers a new medium for presentation of financial reports by companies. New applications, new users and faster connections have spurred the Internet to become an important medium for communication, information dissemination and commerce. The need for information disclosure stems from market failures caused by low disclosure of relevant information for users resulting in information asymmetry. The voluntary nature of information provided on the internet by the publicly listed companies has resulted in non- uniformity in their disclosures. The objective of the present study is to test whether is any significant influence of market capitalization, debt-asset ratio, financial performance, profit level, and stock price on Internet Financial Reporting (IFR) Disclosure Index and the tests are conducted by measuring IFR index of as a dependent variable and the above five independent variables in 32 banking sample companies selected from BSE-500. The results indicated that IFR index of Indian banking sector was very strongly associated with market capitalization.